2012
DOI: 10.1371/journal.pgen.1002708
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of a Novel FGF23 Regulator, FAM20C, Leads to Hypophosphatemic Rickets in Mice

Abstract: Family with sequence similarity 20,-member C (FAM20C) is highly expressed in the mineralized tissues of mammals. Genetic studies showed that the loss-of-function mutations in FAM20C were associated with human lethal osteosclerotic bone dysplasia (Raine Syndrome), implying an inhibitory role of this molecule in bone formation. However, in vitro gain- and loss-of-function studies suggested that FAM20C promotes the differentiation and mineralization of mouse mesenchymal cells and odontoblasts. Recently, we genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
195
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(210 citation statements)
references
References 58 publications
(106 reference statements)
11
195
0
4
Order By: Relevance
“…MC3T3-E1 cells regularly do not express an osteocytic phenotype; however, long culture under osteogenic differentiation medium reportedly allows these cells to produce an osteocytic phenotype, such as that involving the DMP1 or FGF23 production (Figure 5a). 47 Treatment of the long-cultured MC3T3-E1 cells with DMP1 (100 ng ml À 1 ) significantly downregulated fgf23 expression, whereas endogenous Dmp1 expression level was significantly upregulated (Figure 5b). These findings were consistent with the observations in UMR106 cells, although other markers that we investigated did not show significant changes in the long-cultured MC3T3-E1 cells (Figure 5b).…”
Section: Direct Regulation Of Fgf23 By Dmp1mentioning
confidence: 94%
See 1 more Smart Citation
“…MC3T3-E1 cells regularly do not express an osteocytic phenotype; however, long culture under osteogenic differentiation medium reportedly allows these cells to produce an osteocytic phenotype, such as that involving the DMP1 or FGF23 production (Figure 5a). 47 Treatment of the long-cultured MC3T3-E1 cells with DMP1 (100 ng ml À 1 ) significantly downregulated fgf23 expression, whereas endogenous Dmp1 expression level was significantly upregulated (Figure 5b). These findings were consistent with the observations in UMR106 cells, although other markers that we investigated did not show significant changes in the long-cultured MC3T3-E1 cells (Figure 5b).…”
Section: Direct Regulation Of Fgf23 By Dmp1mentioning
confidence: 94%
“…To detect the expression of FGF23 in these cells, we performed long-term culture with osteogenic medium over 4 weeks, modified as previously described. 47 After 4 weeks of culture in the culture dish, the cells were seeded onto well plates for each assay.…”
Section: Animals and Preparation Of Skeletal Tissuesmentioning
confidence: 99%
“…Our MS data confirmed that KO-derived DMP1 had less phosphorylation than that of WT mice. In an earlier study, we reported significant down-regulation of DMP1 in the Fam20C-KO mice (25). It is unclear whether the lower levels of expression and phosphorylation of DMP1 in the KO mice were related to the different MS coverage of the WT-and KO-derived proteins.…”
Section: Discussionmentioning
confidence: 85%
“…Fam20C-KO mice mediated by Sox2-Cre were generated by a published process (25). The animal procedures were performed in accordance with the U.S. National Institutes of Health Guide for the Care and Use of Laboratory Animals and approved by the Animal Care and Use Committee of Texas A&M University Baylor College of Dentistry.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation